STRATEGIES AND NEW MODELS FOR SOCIAL DEVELOPMENT - Pejkovski, Jovan (Ревија за социјална политика/Journal of Social Policy, 2015)
Strategic planning is the process of formulating and implementing strategies with which the organizations and the institutions are adjusted and influenced on the changes in the environment. Understanding of the future and the need for strategic determination of the conditions and possibilities for its achievement is crucial question of each society. Creating a strategy cannot be understood as a magic solution to the problems because it is a way to deal with the problems and risks that will appear in a structured way. Creating strategy represents a new way of thinking, and accordingly creates new skills to be able to carry out the process. But it also must be flexible and adapt to the characteristics and specifications of each organization. With including of the key elements of the strategic planning process successful strategic prediction is achieved aimed at decisionmaking procedure related to the organization of the system and the environment in the future. The impacts of globalization but also many international organizations and funds will imply the needs for the preparation of strategies that are derived from strategic planning. Organizations, institutions, whether public or private, should be developed in subjects that